Construal-level priming does not modulate memory performance in Deese-Roediger/McDermott paradigm. Issue 9 (20th October 2020) - Tse, Chi-Shing; Gu, Xuan; Zeng, Taoran; Chan, Yuen-Lai
ABSTRACT: Construal level refers to the level of abstractness that events and objects are represented, with high construal level promoting relational processing, whereas low construal level, item-specific processing. Three experiments (total N  = 432) were conducted to investigate how priming construal level affects encoding of Deese/Roediger-McDermott (DRM) lists (e.g., bed, dream   … converged to a critical item sleep ), and then modulates free recall and recognition memory performance. Before and during list encoding, participants were primed with high/low construal level by identifying global/local letter in composite letters in a Navon task, choosing category (e.g., body)/exemplar (e.g., liver) to common objects (e.g., internal organ) in a two-alternative-forced-choice task, or by narrating on a particular incident they had power over other people or someone else had power over them. Half of critical items (and yoked associates) were studied and half were not, so their hit rates, false alarm rates, and memory sensitivity were measured. Results showed the typical false memory effect and lower memory sensitivity for critical items (vs. yoked associates), but there was no significant effect of primed construal level on memory performance in all experiments, despite our sample sizes ensuring strong statistical power. Hence, construal-level priming does not modulate memory performance in the DRM task.